IMPACT OF USE OF SOCIAL APPLICATIONS AND APPEARANCE-RELATED CONSCIOUSNESS ON BODY DYSMORPHIC DISORDER SYMPTOMS AND LOWER SELF-ESTEEM AMONG FEMALES - Waqar, Laiba; Mazhar, Arooj Fatima; Rafique, Maria; Rehman, MIsbah (Journal of Pakistan Psychiatric Society, 2022)
Objective: To investigate the impact of use of social applications and appearance-related consciousness on Body dysmorphic disorder symptoms and lower self-esteem among females.Research Design: Study uses cross-sectional research design to examine the association of social applications and appearance-related consciousness with symptoms of body dysmorphic disorder and lower self-esteem.Place and duration of study: The study was conducted in 6 months at Riphah International University from January to August 2022.Methods: A total of 200 females were approached via convenience sampling for this study from universities, colleges and workplace of Pakistan. Female participants of age range young adults i. e. 17-35 years were included in study. Females actively using social media for more than 6 months were recruited.Results:  According to the results it was found that social application use and appearance-related conciseness both were positively related to symptoms of body dysmorphic disorder. However, it was showed that social application use and appearance-related conciseness were negatively related to self -esteem.Conclusion: The present study demonstrated that individuals who excessively use social applications and are more likely to be unhappy with their own body image and experience more negative feelings after viewing appealing self-images on social media. Higher body dysmorphic and worse self-esteem were revealed to be positively correlated with appearance-related awareness.